FRI0329 Free light chains of immunoglobulins in serum as biomarkers of activity in systemic lupus erythematosus. (23rd January 2014) - Hrncir, Z.; Drahosova, M.; Soukup, T.; Toms, J.
Abstract : Background: The molecules of immunoglobulins (Ig) include two identical heavy and two identical light chains. More light than heavy chains of Ig are produced under physiological conditions, and so free light chains (FLC) may be detected in biological fluids, especially in serum. Systemic lupus eryhtematosus (SLE) is associated with polyclonal activation of B cells, and proportional elevation of FLC kappa and FLC lambda values in serum should be expected in active form of SLE. Objectives: To explore the changes of serum concentration of FLC kappa and FLC lambda as putative biomarkers of SLE disease activity in a prospective, comparative, and cross-over study. Methods: Eighty-three adult SLE pts (ACR/1982, updated 1997) and 33 age- and sex-matched healthy controls were enrolled; concomitant infection, monoclonal gammopathy and renal failure in SLE pts were excluded. Disease activity was assessed using the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K): a score ≥ 6 was considered clinically important. FLC kappa and FLC lambda in serum were analysed by quantitative nephelometric assay (Freelite, The Binding Site Group, Birmingham, UK) and compared against SLEDAI-2K score and serological biomarkers IgG, C3, C4 (Beckman Coulter), "total" ANA/IF (DIA SORIN, USA) in maximal titre, anti-dsDNA/IFCL (INOVA, USA) in maximal titre, and antinucleosome Abs/ELISA (EUROIMMUN, BRD). The data obtained were statistically processed using Medcalc-Statistical Software progamme. Results: Serum concentration of FLC kappa, FLC lambda and total FLC kappa+FLC lambda in 22 SLE with SLEDAI-2K ≥ 6, and also in 61 SLE with SLEDAI-2K < 6 was significantly higher against healthy controls (p=0.003- < 0.001) except FLC lambda in SLE with SLEDAI-2K < 6 (p > 0.05). In SLE with SLEDAI-2K ≥ 6 the concentration of FLC kappa, FLC lambda and FLC kappa+FLC lambda was always significantly higher than in SLE with SLEDAI-2K < 6 (p < 0.001). In total group of 83 SLE was found significant correlation (p < 0.001) between SLEDAI-2K score and FLC kappa (r = 0.56), FLC lambda (r = 0.58), and FLC kappa+FLC lambda (r = 0.62); FLC analysis against serological biomarkers under study demonstrated a strong correlation namely between antinucleosome Abs and FLC kappa (r = 0.59), FLC lambda (r = 0.53) and FLC kappa+FLC lambda (r = 0.59). Conclusions: The data obtained are suggesting that investigation of FLC values in serum should be useful as biomarkers of SLE disease activity, but further studies are necessary. Disclosure of Interest : Z. Hrncir Grant/research support from: PRVOUK P37-08, M. Drahosova Grant/research support from: PRVOUK P37-08, T. Soukup: None Declared, J. Toms: None Declared